1998
DOI: 10.1021/jf970745x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Mobility of Sulfometuron-methyl (Oust Herbicide) in Field Soil

Abstract: The degradation and mobility of sulfometuron-methyl and potential degradates were evaluated under actual field conditions in the United States following application of Oust herbicide to bare ground at the maximum labeled rate. Sulfometuron-methyl degraded rapidly at the four test sites; calculated half-life (t 1/2) values ranged from 12 to 25 days. Sulfometuron-methyl residues were below the limit of quantitation (10 ppb) beyond 90 days after treatment (DAT) at all test sites. The highest degradate concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…This cyclization degradation pathway that generated compound 2 is unusual with the sulphonylurea herbicides. It was not observed with the sulphonylureas benzene–triazine metsulfuron and the benzene–pyrimidine sulfometuron, in spite of the carbomethoxy group on the benzene ring in ortho to the sulfonylurea bridge (Anderson et al ., 1989; Trubey et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This cyclization degradation pathway that generated compound 2 is unusual with the sulphonylurea herbicides. It was not observed with the sulphonylureas benzene–triazine metsulfuron and the benzene–pyrimidine sulfometuron, in spite of the carbomethoxy group on the benzene ring in ortho to the sulfonylurea bridge (Anderson et al ., 1989; Trubey et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolite 3 was generated by bridge contraction, in the same way as the pyridine–pyrimidine rimsulfuron in soil (Schneiders et al ., 1993; Rouchaud et al ., 1997). The benzene–triazine sulfonylureas metsulfuron in wheat and sulfometuron in soil, and the thiophene–triazine sulfonylurea thifensulfuron in soil did not, however, generate the corresponding amine by bridge contraction (Anderson et al ., 1989; Cambon et al ., 1998; Trubey et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Trubey et al 8 have reported that sulfometuron-methyl underwent the cleavage of sulfonylurea bond under aerobic upland conditions. From these findings, it was assumed that imazosulfuron in upland soils underwent the hydrolysis of sulfonylurea bond to give ADPM and IPSN.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous layer was extracted with ether (2x75 ml), and the organic fractions were combined, not dried, filtered, evaporated, and recrystallized to afford product. [2][3]4,)benzenesulfonamide (4a).…”
Section: Methodsmentioning
confidence: 99%